The FiCTION trial: Child oral health‐related quality of life and dental anxiety across three treatment strategies for managing caries in young children. Issue 4 (27th April 2020) - Freeman, Ruth; Maguire, Anne; Ryan, Vicky; Wilson, Nina; Innes, Nicola P.T.; Clarkson, Jan E.; McColl, Elaine; Marshman, Zoe; Robertson, Mark; Abouhajar, Alaa; Chadwick, Barbara; Deery, Christopher; et al.
Abstract: Objectives: The FiCTION trial compared co‐primary outcomes (dental pain and/or infection) and secondary outcomes (child oral health‐related quality of life [COHRQOL], child dental anxiety, cost‐effectiveness, caries development/progression and acceptability) across three treatment strategies (Conventional with Prevention [C + P]; Biological with Prevention [B + P]; Prevention Alone [PA]) for managing caries in children in primary care. COHRQOL and child dental anxiety experiences are reported upon here. Methods: A multi‐centre, 3‐arm, parallel‐group, unblinded patient‐randomized controlled trial of 3‐ to 7‐year‐olds treated under NHS contracts was conducted in 72 general dental practices in England, Wales and Scotland. Child participants (with at least one primary molar with dentinal caries) were randomized (1:1:1) to one of three treatment arms with the intention of being managed according to allocated arm for 3 years (minimum 23 months). Randomization was via a centrally administered system using random permuted blocks of variable length. At baseline and final visit, accompanying parents/caregivers completed a parental questionnaire including COHRQOL (16 item P‐CPQ‐16), and at every visit, child‐ and parental‐questionnaire‐based data were collected for child‐based dental trait and state anxiety. Statistical analyses were conducted on complete cases from the modified intention‐to‐treat (mITT) analysis set. Results: A total of 1144 children were randomized (C + P: 386; B + P: 381; PA: 377). The mITT analysis set included the 1058 children who attended at least one study visit (C + P: 352; B + P: 352; PA: 354). Median follow‐up was 33.8 months (IQR: 23.8, 36.7). The P‐CPQ‐16 overall score could be calculated after simple imputation at both baseline and final visit for 560 children (C + P: 189; B + P: 189; PA: 182). There was no evidence of a difference in the estimated adjusted mean P‐CPQ‐16 at the final visit which was, on average, 0.3 points higher (97.5% CI: −1.1 to 1.6) in B + P than C + P and 0.2 points higher, on average, (97.5% CI: −1.2 to 1.5) in PA than for C + P. Child dental trait anxiety and child dental state anxiety, measured at every treatment visit, showed no evidence of any statistically or clinically significant difference between arms in adjusted mean scores averaged over all follow‐up visits. Conclusions: The differences noted in COHRQOL and child‐based dental trait and dental state anxiety measures across three treatment strategies for managing dental caries in primary teeth were small, and not considered to be clinically meaningful. The findings highlight the importance of including all three strategies in a clinician's armamentarium, to manage childhood caries throughout the young child's life and achieve positive experiences of dental care.